Detection accuracy of the Cobas HPV assay for high‐risk HPV in head and neck FNA biopsy specimens. Issue 7 (22nd February 2022) - Guo, Ming; Khanna, Abha; Tinnirello, Agata A.; Hwang, Jessica; Zhang, Ping; Xu, Li; Li, Guojun; Dahlstrom, Kristina R.; Sturgis, Erich M.; Stewart, John
Abstract : BACKGROUND: This study evaluated the detection accuracy of the Cobas human papillomavirus (HPV) assay for high‐risk human papillomavirus (hrHPV) and HPV‐16 in head and neck fine‐needle aspiration (FNA) specimens with squamous cell carcinoma. METHODS: Head and neck FNA biopsy specimens from 2012 to 2020 were retrospectively collected. Cobas HPV testing was performed on 90 FNA specimens with valid Cervista HPV testing results. Results of Cobas HPV and Cervista HPV assays were compared. A Linear Array or SPF10‐LiPA25 HPV genotyping assay resolved cases with discrepant results. The κ value and accuracy of Cobas HPV testing were calculated. The accuracy of the Cobas HPV assay was also determined in 42 FNA needle‐rinse specimens. RESULTS: Cobas HPV was positive in 82% of the FNA specimens (74 of 90). The concordance between Cobas HPV and Cervista HPV test results was 88.9% (80 of 90) with substantial agreement (κ = 0.669; 95% CI, 0.481‐0.856). With HPV genotyping confirmation in cases with discrepant results between the 2 HPV assays, Cobas HPV showed 100% sensitivity and specificity for hrHPV. HPV‐16 was detected in 88% of HPV‐positive cases (65 of 74). HPV genotyping confirmed 1 false‐negative HPV‐16 result and 1 false‐positive HPV‐16 result. Overall, the accuracy of Cobas HPV for HPV‐16 was 97.8%. The accuracy of Cobas HPV in FNA needle‐rinse specimens was 100%. CONCLUSIONS: The Cobas HPV assay is highly accurate for determining the HPV status in head and neck FNA specimens. FNA needle rinse is valid for Cobas HPV testing in patients with squamous cell carcinoma.;